P‐82: Improved Methodology for Testing Edge Strength for Ultra‐Thin Panels. Issue 1 (30th May 2018) - Agnello, Gabriel; Tremper, Amber; Li, Weidong; Knowles, Peter
Abstract : Traditional testing methodologies (four point bend and three point bend) have limited effectiveness as panel thicknesses decrease due to a variety of interconnected factors. This limited effectiveness impacts the ability to make reliability predictions based on edge strength measurements. This paper provides an improved methodology for testing the edge strength of ultra‐thin panels for reliability predictions through a system of rollers strategically placed only at the edge of the glass panel.